Improving Science Learning Outcomes Through Stratetic Intervention Materials: A Contextualized Approach for Grade 6 Learners - Lituanas, Aljim B.; Dela Cruz, Fe M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
A study aimed to develop a Strategic Intervention Material (SIM) in science for Grade 6 learners at Tungao Central Elementary School. Observations showed that many students struggled with core science concepts, specifically differentiating between solutes and solvents, describing suspensions, and understanding mixture separation methods such as decantation and the use of magnets. Student performance on first-quarter science tests was evaluated, with 91 learners participating. Two experts assessed the SIMs for quality, accuracy, relevance, and contextualization, leading to refinements. The developed SIMs include guide cards, activity cards, assessment cards, enrichment activities, reference cards, and answer keys. Results highlight the crucial need for context-specific educational interventions to address learning deficits in science. Incorporating contextually relevant materials can significantly enhance teaching effectiveness and student learning outcomes. The contextualized SIMs offer a practical solution for improving student comprehension and performance in challenging scientific concepts, thereby contributing to more effective teaching and learning strategies within the local educational context.